The Politics of Production in the Engineering Industry. Issue 1 (April 2016) - Whitston, Kevin
Abstract : This article seeks to connect work and politics in the engineering industry in the twentieth century. It is about how shared identities were created from overlapping and conflicting shop-floor interests and the political ambiguities generated by this experience. There is still much to be said for Hobsbawm's account of how the workplace experience of the engineering craftsmen drew many to revolutionary politics but it captures only part of the story. The experience that led some craftsmen to the Communist Party persuaded others to disengage from politics and some to cut their links with craft altogether, joining the sections set up for the union's industrial membership. Semi-skilled and unskilled workers were integrated in shop-floor trade unionism but, like the skilled men who opted for industrial membership, left the business of the 'The Union' to others. Militant trade unionism and the intensely political internal life of the union masked a deeper political alienation.